Chemical Behavior and Bioactive Properties of Spinorphin Conjugated to 5,5'-Dimethyl- and 5,5'-Diphenylhydantoin Analogs - Stela Georgieva; Petar Todorov; Jana Tchekalarova; Subaer Subaer; Petia Peneva; Kalin Chakarov; Hartati Hartati; Sitti Faika (MDPI AG, 2024)
The discovery of new peptides and their derivatives is an outcome of ongoing efforts to identify a peptide with significant biological activity for effective usage as a possible therapeutic agent. Spinorphin peptides have been documented to exhibit numerous applications and features. In this study, biologically active peptide derivatives based on novel peptide analogues of spinorphin conjugated with 5,5'-dimethyl (Dm) and 5,5'-diphenyl (Ph) hydantoin derivatives have been successfully synthesized and characterized. Scanning electron microscopy (SEM) and spectral methods such as UV-Vis, FT-IR (Fourier Transform Infrared Spectroscopy), CD (Circular Dichroism), and fluorimetry were used to characterize the microstructure of the resulting compounds. The results revealed changes in peptide morphology as a result of the restructuring of the aminoacidic sequences and aromatic bonds, which is related to the formation of intermolecular hydrogen bonds between tyrosyl groups and the hydantoin moiety. Electrochemical and fluorescence approaches were used to determine some physicochemical parameters related to the biological behavior of the compounds. The biological properties of the spinorphin derivatives were evaluated in vivo for anticonvulsant activity against the psychomotor seizures at different doses of the studied peptides. Both spinorphin analog peptides with Ph and Dm groups showed activity against all three phases of the seizure in the intravenous Pentylenetetrazole Seizure (ivPTZ) test. This suggests that hydantoin residues do not play a crucial role in the structure of spinorphin compounds and in determining the potency to raise the seizure threshold. On the other hand, analogs with a phenytoin residue are active against the drug-resistant epilepsy test (6-Hz test). In addition, bioactivity analyses revealed that the new peptide analogues have the potential to be used as antimicrobial and antioxidant compounds. These findings suggest promising avenues for further research that may lead to the development of alternative medicines or applications in various fields beyond epilepsy treatment.